Studies on the effectiveness of diarylheptanoids derivatives against Leishmania amazonensis - Catarina AC Araujo; Leila V Alegrio; Denise CF Gomes; Marco Edilson F Lima; Leonardo Gomes-Cardoso; Leonor L Leon (Memorias do Instituto Oswaldo Cruz, 1999)
In a previous work we demonstrated that diarylheptanoids extracted from Centrolobium sclerophyllum are very active against Leishmania amazonensis promastigotes. In order to continue our studies with these class of compounds, we decided to evaluate the activity of several diarylheptanoids derived from curcumin (diferuloyl methane) against the extracellular form (promastigotes) of L. amazonensis. Furthermore, an experiment against the intracellular form of the parasite (amastigotes) was carried out, comparing the most active compound among the curcumin derivatives (the methylcurcumin) with des-O-methylcentrolobine, the most active diarylheptanoid derived from C. sclerophyllum.